Anti-cancer properties of low-molecular-weight heparin: Preclinical evidence - Mousa, Shaker A.; Petersen, Lars J. (Thrombosis and Haemostasis, 2009)
Malignant conditions are frequently associated with a hypercoaguable state, with recurrent thrombosis due to the impact of cancer cells and chemotherapy or radiotherapy on the coagulation cascade. Heparin and, its pharmacokinetically improved versions, low-molecular-weight heparins (LMWH) are effective in the prevention and treatment of thromboembolic events in cancer patients. There are several lines of preclinical evidence suggesting potential benefits of LMWH in hypercoagulation and thrombosis as well as in various processes involved in tumour growth and metastasis.Tinzaparin is a LMWH produced by controlled enzymatic depolymerisation of unfractionated heparin. The efficacy of tinzaparin has been documented in several clinical trials across various conditions and in special patient populations.The main objective of this review is to present the existing knowledge on the preclinical anti-cancer properties of tinzaparin and other LMWH.The evidence for tinzaparin, as well as other LMWH, regarding interference with cancer-induced hypercoagulation, cancer cell proliferation, degradation of extra-cellular matrix, angiogenesis, selectin-mediated binding of platelet and cancer cells, chemokine signalling, tumour progression, and metastasis are reviewed. Certain clinical trials suggest improved survival of cancer patients with deep venous thrombosis treated with LMWH versus unfractionated heparin and when added to the promising preclinical anti-cancer properties of LMWH this warrants further investigations in prospective, randomised, controlled clinical trials in cancer patients.The benefits of LMWH in cancer might at least in part, be independent from its anti-coagulant activities, but may still be partially dependent on its anti-coagulant activities.
Keywords: Heparin; low-molecular-weight heparin; thrombosis; cancer; metastasis; tissue factor; tissue factor pathway inhibitor; selectin; angiogenesis; cancer-associated thrombosis; deep venous thrombosis; prophylaxis; treatment